2004
DOI: 10.1111/j.1460-9568.2004.03761.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐immunoreactive starburst amacrine cells in pigmented and albino rats

Abstract: In this study we tested whether the critical anatomical substrate for retinal direction selectivity is altered in albino mammals. We used dual immunostaining for GABA and choline acetyltransferase and quantitatively analyzed the number of double-labelled starburst amacrine cells in wild-type and albino rats. In albino rats, the percentage of ON-amacrine cells with high GABA content was significantly lower than in pigmented animals. OFF-amacrines did not significantly differ between the two rat strains. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…ON-amacrine cells contribute to the generation of direction selectivity of ganglion cell response innervating the opto-kinetic system. Although the authors discuss that the difference found in GABA-rich ON-starburst amacrine cells may be too subtle to explain the drastic physiological alterations seen in albino rats, at least some of these alterations could be caused by the smaller number of amacrine cells [7]. Donatien et al [12] reported on a reduced ganglion cell density in albino rabbits.…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…ON-amacrine cells contribute to the generation of direction selectivity of ganglion cell response innervating the opto-kinetic system. Although the authors discuss that the difference found in GABA-rich ON-starburst amacrine cells may be too subtle to explain the drastic physiological alterations seen in albino rats, at least some of these alterations could be caused by the smaller number of amacrine cells [7]. Donatien et al [12] reported on a reduced ganglion cell density in albino rabbits.…”
Section: Figmentioning
confidence: 97%
“…Except for a slightly reduced number of ganglion cells, no obvious anatomical differences with respect to horizontal, amacrine or ganglion cells were found between albino and pigmented rats. Nevertheless, there are less GABA-rich ON-starburst amacrine cells in Wistar rats than in Long-Evans rats, which could be indicate differences in the retinal neuronal circuitry [7]. ON-amacrine cells contribute to the generation of direction selectivity of ganglion cell response innervating the opto-kinetic system.…”
Section: Figmentioning
confidence: 99%
“…Differences between pigmented and albino in the distribution of other retinal cell types have been identified in previous studies. Amacrine cell populations and the ganglion cell population have been shown to be disrupted in the albino phenotype in a variety of rodent and carnivore species (Stone et al ., 1978; Morgan et al ., 1987; Oyster et al ., 1987; Mitrofanis & Stone, 1988; Jeffery & Kinsella, 1992; Donatien et al ., 2002; Blaszczyk et al ., 2004). In contrast, the horizontal cell distribution appears normal in albino mouse (Raven & Reese, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest defects of specific cell populations in the albino retina. One amacrine cell subpopulation is increased in number in albino rats and Siamese cats (Mitrofanis & Stone, 1988) whereas another is significantly decreased in number in albino rats (Blaszczyk et al ., 2004). Estimates of ganglion cell numbers show a decrease in the Siamese cat, albino rabbit and albino ferret (Stone et al ., 1978; Morgan et al ., 1987; Oyster et al ., 1987; Jeffery & Kinsella, 1992; Donatien et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation